Extrachromosomal, homologous expression of trypanothione reductase and its complementary mRNA in Trypanosoma cruzi. - Tovar, J (1996)
Trypanothione reductase (TR), a flavoprotein oxidoreductase present in trypanosomatids but absent in human cells, is regarded as a potential target for the chemotherapy of several tropical parasitic diseases caused by trypanosomes and leishmanias. We investigated the possibility of modulating intracellular TR levels in Trypanosoma cruzi by generating transgenic lines that extrachromosomally overexpress either sense or antisense TR mRNA. Cells overexpressing the sense construct showed a 4-10-fold increase in levels of TR mRNA, protein and enzyme activity. In contrast, recombinant T.cruzi harbouring the antisense construct showed no significant difference in TR protein or catalytic activity when compared with control cells. Although increased levels of TR mRNA were detected in some of the antisense cells neither upregulation nor amplification of the endogenous trypanothione reductase gene (tryA) was observed. Instead, a proportion of plasmid molecules was found rearranged and, as a result, contained the tryA sequence in the sense orientation. Plasmid rescue experiments and sequence analysis of rearranged plasmids revealed that this specific gene inversion event was associated with the deletion of small regions of flanking DNA.